ANALISIS PENDAPATAN PG.XYZ DI JAWA TIMUR - Mohammad Ali Masruri; Anita Handayani (Universitas 45 Surabaya, 2023)
This study purpose to know the company’s income PG. XYZ East Java company. Income analysis is used to know whether the business development is increasing or decreasing. Considering the income earned affects to the survival of the company. The type of research used is descriptive qualitative research. Data analysis method is used quantitative methods, namely descriptive analysis. The evaluation results show that the average net income earned by the East Java PG.XYZ sugar business is IDR 362,862,000/year or IDR. 30,238,500/month and the sugar business run by PG. XYZ East Java is profitable. It can be seen from the acquisition of a ratio analysis of more than 1, namely 1.21. Therefore, it is hoped that PG. XYZ East Java will continue to develop its sugar business and increase sales volume so that its income will also increase.